Direct growth of vertically aligned single-walled CNTs on conducting substrate and its electrochemical performance in ionic liquids - Mohd Abid, Mohd Asyadi Azam; Isomura , Kazuki; Fujiwara, Akihiko; Shimoda, Tatsuya (2013)
We report fabrication of vertically-aligned single-walled carbon nanotube (VA-SWCNT) electrodes for a symmetric electrochemical capacitor using a simple ethanol-based CNT growth system. From the CNT direct growth technique, the electrode was easily prepared, and consequently assembled with ionic liquid as electrolyte. VA-SWCNTs were directly grown on conducting SUS 310S foils in which the binder material was not incorporated in the capacitor structure. This capacitor demonstrated excellent gravimetric capacitance and a high rate capability. From the cyclic voltammetric analysis, the capacitance was contributed not only from the ideal double layer capacitance, but also from faradaic processes that might have occurred during charge-discharge. Other than the capacitance, the VA-SWCNT capacitor was also measured by using frequency response (impedance) and charge-discharge analyses.